AMI, an Indazole Derivative, Improves Parkinson’s Disease by Inhibiting Tau Phosphorylation - Mao, Zhang; Wen-ting, Zhu; Hai-tao, Wang; Hui, Yu; Shi-yi, Lan; Jiang-ping, Xu; Wen-ya, Wang (Frontiers in Molecular Neuroscience, 2020)
Dopaminergic neuronal loss is the main pathological character of Parkinson’s disease (PD). Abnormal tau hyperphosphorylation will lead to dopaminergic neuronal loss. An indazole derivative 6-amino-1-methyl-indazole (AMI) successfully synthesized to inhibit tau hyperphosphorylation may exert a neuroprotective effect. The in vitro study showed that AMI effectively increased cell viability and alleviated the apoptosis induced by MPP+ in SH-SY5Y cells. In addition, AMI treatment significantly decreased the expression of p-tau and upstream kinases GSK-3β. In the MPTP-induced PD mice models, we found AMI apparently preserved dopaminergic neurons in the substantia nigra and improved the PD behavioral symptoms. Our results demonstrate that AMI exerts a neuroprotective effect by inhibiting tau hyperphosphorylation, representing a promising new candidate for PD treatment.